FACTORS INFLUENCING CUSTOMER PURCHASE INTENTION VIA FACEBOOK LIVE STREAM AT EVER CLOTHINGS MANADO - Esther Pamela Adeleida Malonda; David P. E. Saerang; Shinta J. C. Wangke (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
One way to get customers to make purchases via Facebook Live Streaming is to analyze the factors that influence customer purchase intentions. The purpose of this research was to analyze the factors that influence Customer Purchase Intention via Facebook Live Streaming at Ever Clothings Manado. This research used the quantitative method with factor analysis techniques. The sample of this research is 100 samples which are customer of Ever Clothing Manado. At the beginning of the research there twenty factors that are determined as material for testing and research. After doing the analysis, the result showed that two variables must be eliminated because the extraction value of this variable is less than 0.5, and only eighteen variables can be used. From the 18 variables, 4 new factors were formed which are: Popularity of Facebook Account, Quality of Products, Quality of Seller, and Seller Communication Ability.   Keywords: digital marketing, Facebook live stream, purchase intention, Facebook account popularity, quality of products, quality of seller, seller communication ability, factor analysis